2021
DOI: 10.1055/s-0042-1750281
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Treat Sensorineural Hearing Loss by Hair-Cell Regeneration: The Current State of Therapeutic Developments and Their Potential Impact on Audiological Clinical Practice

Abstract: Sensorineural hearing loss (SNHL) is typically a permanent and often progressive condition that is commonly attributed to sensory cell loss. All vertebrates except mammals can regenerate lost sensory cells. Thus, SNHL is currently only treated with hearing aids or cochlear implants. There has been extensive research to understand how regeneration occurs in nonmammals, how hair cells form during development, and what limits regeneration in maturing mammals. These studies motivated efforts to identify therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Our ABR results showed that the mice exhibited high-frequency hearing deficits 4 weeks after exposure to PS-NPs, which subsequently worsened at the next 4 weeks of testing ( Figures 2D–H ). The common reason behind sensorineural hearing loss is the injury of hair cells located in the Corti organ of the cochlear auditory sensory epithelium ( Hinton et al, 2021 ). To investigate hair cell pathology caused by PS-NPs, we observed the hair cells of mice by experimental preparation of cochlear epithelia for hair cell staining, and we performed scanning electron microscopy observations of the cochlea stereocilia as well as H&E staining.…”
Section: Resultsmentioning
confidence: 99%
“…Our ABR results showed that the mice exhibited high-frequency hearing deficits 4 weeks after exposure to PS-NPs, which subsequently worsened at the next 4 weeks of testing ( Figures 2D–H ). The common reason behind sensorineural hearing loss is the injury of hair cells located in the Corti organ of the cochlear auditory sensory epithelium ( Hinton et al, 2021 ). To investigate hair cell pathology caused by PS-NPs, we observed the hair cells of mice by experimental preparation of cochlear epithelia for hair cell staining, and we performed scanning electron microscopy observations of the cochlea stereocilia as well as H&E staining.…”
Section: Resultsmentioning
confidence: 99%
“…Because SNHL results from permanent damage to and loss of cochlear hair cells, a fair portion of therapeutic research has set out to explore the potential of hair cell regeneration [136]. Presently, three companies have advanced preclinical data into clinical works, and these have been outlined and well described in a recent review by Hinton et al Briefly, clinical hair cell regeneration therapies primarily embrace gene therapy and small molecule inhibitor or combination approaches [137].…”
Section: Additional Therapiesmentioning
confidence: 99%
“…Emerging understanding of the mechanisms of transcription factors that induce HC differentiation (Atkinson et al, 2014 ;Bermingham et al, 1999 ;Garcia-Anoveros et al, 2022 ;Zheng and Gao, 2000 ), and potential induction for regeneration are promising, but none have produced new HCs with sustained functions (Iyer et al, 2022b ;Zine et al, 2021 ). Thus, the current treatment for hearing loss ensuing from HC loss is cochlear implants, despite the potential advantages of HC-replacement therapy (Hinton et al, 2021 ;Sullivan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%